Improving Students' Writing Achievement in Narrative Texts Using Picture Series - Nia Prasti Andini; Cucu Sutarsyah; Khairun Nisa (U-Jet Unila Journal of English Language Teaching, 2026)
This study aims to find out whether the use of picture series can improve students’ writing achievement in narrative texts at the ninth grade of SMP Kartika II-2 Bandar Lampung. This research applied a quantitative method with a one-group pre-test and post-test design. One class was selected as the sample and the data were collected through writing tests. The data were analyzed using a paired sample t-test to examine whether there was a significant difference between the pre-test and post-test scores. The results of the t-test showed that there was a significant difference between students’ pre-test and post-test scores in students’ writing achievement. The mean score increased from 63.65 in the pre-test to 82.18 in the post-test, with a mean difference of 18.53. This indicates that students’ writing achievement improved after being taught using picture series. Therefore, picture series can be considered as an effective medium to improve students’ writing achievement in narrative texts at the junior high school level.